Modified Explant Culture is the Effective Technique for Isolating Mesenchymal Stem Cells from Glioblastoma - Zamani, Farshid; Oraee Yazdani, Saeed; Heidari, Neda; Yeganeh, Farshid; Karima, Saeed; Hashemi, Seyed Mahmoud (Student Research in Translational Medicine, 2022)
Background and Aim: Until now, mesenchymal stem cells (MSCs) have been obtained from a variety of sources, including several tumor types. In order to acquire cells with the best quality and function while also taking economic factors into account, selecting an appropriate isolation procedure is a crucial step. The goal of this study was to use a modified explant culture approach to isolation of pure mesenchymal stem cells from human glioblastoma. Methods: Six samples of glioblastoma tumors were cut into cube - like fragments of 1-3 mm in diameter (explants). The explants were put into the wells of a 24-well plate, cultured in Dulbecco's Modified Eagle's medium (DMEM), and kept at 37°C with 5% CO2 in an incubator. Inverted microscopy was used to analyze the morphological phenotypes of the cells. Wells with uniform fibroblast-like cell morphology were considered positive and chosen for further expansion and identification. Results: Totally, 38.46% of the wells were chosen for development after testing positive for all grown explants. According to flow cytometry analyses, the isolated cells were positive for CD73, CD105, and CD90 but negative for CD45 and CD34. The cells also successfully underwent multipotential differentiation into adipocytes and osteoblasts. Conclusion: Overall, our research demonstrated that GA - MSC could successfully be isolated from human Glioblastoma tumor tissues utilizing a modified explant culture method. With this approach, we were able to rapidly and efficiently develop a more pure MSC population by choosing tumor pieces with the potential to produce a population of homogenous cells with fibroblast - like morphology and removing pieces whose heterogeneous cells were moved. The approach is also workable and affordable. The results might serve as a framework for more investigation into GA - MSCs, glioblastoma TME, and their mechanism of development.